Praktische Fertigkeiten von Schulkindern nach videogestütztem Reanimationstraining = Practical skills of school children after video-based resuscitation training - Müller, A. S.; Weiß, Christel (Notfall & Rettungsmedizin, 2016)
BackgroundLay resuscitation in school gained in importance after a recommendation from the ministers of education and cultural affairs conference in June 2014. Thereby appropriate teaching methods and materials have priority. Five years ago, training of 20,000 school children aged 11-13 years started in South Tyrol using the self-instruction kit MiniAnne®. The purpose of this study was to investigate how well these school children could perform resuscitation 6 months after the MiniAnne® instruction and what should be changed.Material and methodsIn a 5 min resuscitation session, the practical skills of 111 pupils were assessed after a video-based hands-on training using the “Resusci Anne Skill Reporter”.ResultsMore than 96 % performed lay resuscitation. The approach to a resuscitation situation and the necessary actions was done in the correct chronological order by 5.7 %. The correct compression depth was achieved by 1.9 %; the achieved compression depth correlated with weight and sex. Only 3.8 % of the pupils succeeded in ventilating the mannequins. The no-flow fraction was 34.4 %.ConclusionPractical implementation is limited. We suggest to improve and to simplify the teaching material and to repeat exercises in higher grades. This serves to generate experience and the approach to the targets by involving the adolescents’ physical growth. The concrete recommendations refer to MiniAnne® instructions, but the transfer of theory into practice always plays a role in lay resuscitation so that the recommendations are, in principle, independent of the teaching method.